THE GENUS CAREX IN MALAYSIA - E. NELMES (Reinwardtia, 1951)
This is a fully descriptive account of the 108 species of Carex known to occur in Malaysia. They are arranged in three subgenera: Subgenus Indocarex Baill. (43 species), Subgenus Carex (Eucarex Coss. et Germ.) (57 species), and Subgenus Vignea (P. Beauv.) Nees (8 species). These are in turn divided into 33 sections. The classi- fication of these Malaysian Carices differs radically from past systems (cf. that of Kiikenthal, Engl. Pflanzenreich, 1909) and is based on the phylogenetic views of the author. Following the descriptions are citations of all the specimens seen by the author, and a few not seen but which have mainly been determined' by Kiikenthal. The majority of the specimens Came from Bogor (Buitenzorg) (about 1500 sheets) and Leiden (about 600, including important historical specimens). About half of the species are restricted (endemic) to one or another of the 'island areas' into which Malaysia can be conveniently divided: 18 species in New Guinea, 10 in the Philippines, 5 in Borneo and in Sumatra, 4 in the Malay Peninsula, 3 in Java and in Celebes, 2 in the Moluccas, and 1 in the Lesser Sunda Islands. The remaining 58 species have a slightly to much wider distribution, the chief connection being with India, and, to a slightly less extent, Japan and China. Keys are provided to the species as a whole, to the subgenera, the sections, and to the species in each section. The introductory part of the work explains, among other things, the classi- fication, the relative taxonomic value of characters in the descriptions, distribution, and sources of the material,